Does deployment to war affect public service motivation? A panel study of soldiers before and after their service in Afghanistan - Brander, Morten; Andersen, Lotte Bogh (2013)
Exposure to the extreme stress of warfare may affect soldiers' perceptions of others and society. Using panel data from two companies on a tour of duty to Afghanistan in 2011, this article analyzes how different dimensions of soldiers' public service motivation are influenced by deployment to war. As expected, soldiers' compassion decreased and commitment to the public interest increased, while self-sacrifice did not change systematically. Deployment to war was expected to affect inexperienced soldiers more than their experienced colleagues, but this hypothesis was only partially satisfied. The key contribution of the article is the use of panel data and the examination of motivational changes. Moreover, studying soldiers' public service motivation enables us to connect public administration and military sociology and thereby to establish a better understanding of motivation in extreme settings. - Reproduced.
Keywords: Motivation